2012
DOI: 10.5402/2012/102376
|View full text |Cite
|
Sign up to set email alerts
|

Performance Prediction of Solar Adsorption Refrigeration System by Ann

Abstract: This paper proposes a new approach for the performance analysis of a single-stage solar adsorption refrigeration system with activated carbon-R134a as working pair. Use of artificial neural network has been proposed to determine the performance parameters of the system, namely, coefficient of performance, specific cooling power, adsorbent bed (thermal compressor) discharge temperature, and solar cooling coefficient of performance. The ANN used in the performance prediction was made in MATLAB (version 7.8) envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Their results showed that at 295 K as adsorption temperature and 93.33 kPa, the maximum possible adsorption capacity for the nanoporous carbon molecular sieve Carbosieve G (CSG) adsorbent in adsorption of R-11 (CCl 3 F) was 0.735 kg/kg CSG , for R-12 (CCl 2 F 2 ) was 0.644 kg/kg CSG , for R-13 (CClF 3 ) was 0.492 kg/kg CSG , for R-21 (CCl 2 FH) was 0.669 kg/kg CSG , for R-22 (CClF 2 H) was 0.57 kg/kg CSG , for R-23 (CF 3 H) was 0.409 kg/kg CSG , for R-30 (CCl 2 H 2 ) was 0.631 kg/kg CSG , for R-40 (CClH 3 ) was 0.378 kg/ kg CSG , for Nitrogen (N 2 ) was 0.375 kg/kg CSG , for R-114 (CClF 2 -CClF 2 ) was 0.625 kg/kg CSG , for R-114a (CCl 2 -CF 3 ) was 0.581 kg/ kg CSG , for R-115 (CClF 2 -CF 3 ) was 0.477 kg/kg CSG , for R-124 (CClFH-CF 3 ) was 0.505 kg/kg CSG , for R-125 (CHF 2 -CF 3 ) was 0.496 kg/kg CSG , for R-134 (CHF 2 -CHF 2 ) was 0.505 kg/kg CSG and for R-134a (CH 2 F-CF 3 ) was 0.478 kg/kg CSG . From the work of [38] it is pointed out that, all adsorbates tested in this study have high GWP, also R- (11,12,13,21,22,114,115,124) have high ODP.…”
Section: Experimental Workmentioning
confidence: 94%
See 3 more Smart Citations
“…Their results showed that at 295 K as adsorption temperature and 93.33 kPa, the maximum possible adsorption capacity for the nanoporous carbon molecular sieve Carbosieve G (CSG) adsorbent in adsorption of R-11 (CCl 3 F) was 0.735 kg/kg CSG , for R-12 (CCl 2 F 2 ) was 0.644 kg/kg CSG , for R-13 (CClF 3 ) was 0.492 kg/kg CSG , for R-21 (CCl 2 FH) was 0.669 kg/kg CSG , for R-22 (CClF 2 H) was 0.57 kg/kg CSG , for R-23 (CF 3 H) was 0.409 kg/kg CSG , for R-30 (CCl 2 H 2 ) was 0.631 kg/kg CSG , for R-40 (CClH 3 ) was 0.378 kg/ kg CSG , for Nitrogen (N 2 ) was 0.375 kg/kg CSG , for R-114 (CClF 2 -CClF 2 ) was 0.625 kg/kg CSG , for R-114a (CCl 2 -CF 3 ) was 0.581 kg/ kg CSG , for R-115 (CClF 2 -CF 3 ) was 0.477 kg/kg CSG , for R-124 (CClFH-CF 3 ) was 0.505 kg/kg CSG , for R-125 (CHF 2 -CF 3 ) was 0.496 kg/kg CSG , for R-134 (CHF 2 -CHF 2 ) was 0.505 kg/kg CSG and for R-134a (CH 2 F-CF 3 ) was 0.478 kg/kg CSG . From the work of [38] it is pointed out that, all adsorbates tested in this study have high GWP, also R- (11,12,13,21,22,114,115,124) have high ODP.…”
Section: Experimental Workmentioning
confidence: 94%
“…The experimental results also demonstrated that the refrigerator had cooling capacity of 47-78 W during day time and 57.6-104.4 W during night time. From the work of Baiju et al [22] it should be noticed that methanol is a flammable gas and has negative effect on global warming. Glaznev et al [23] introduced a study on composite adsorbents, which were synthesized from a meso-structured silicate (SBA-15) and CaCl 2 , for adsorptive transformation of low temperature heat.…”
Section: Experimental Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The exergy efficiency is found to be maximum in the range between 70 • C and 75 • C. So for the system, the optimum operating point is to be defined. Baiju and Muraleedharan [22] conducted a study on effect of heat source temperature on cycle COP and exergy efficiency of the system. The study reveals that exergy efficiency decreases and cycle COP increases with the increase in heat source temperature.…”
Section: Adsorbent Bedmentioning
confidence: 99%